Emotional Intelligence and Job Satisfaction: A Study of Commercial Bank Employees in the Kathmandu Valley, Nepal - Shrestha, Sampada; Lertjanyakit, Hatairat (Nepalese Journal of Management Science and Research, 2019)
The main aim of this study is to find out the relationship between emotional intelligence and job satisfaction of employees working in the commercial banking sector. Furthermore, the study also tried to determine the relationship between different demographic factors of the employees and emotional intelligence and job satisfaction. The study identifies the how emotional intelligence impact on job satisfaction of employees. For the efficient completion of the research a sample of 394 employees were taken from Kathmandu valley. Convenience sampling method was used for the study. The independent study is completed using a blend of descriptive and inferential analysis. Quantitative method is used in the research where self-administered questionnaire were distributed to the employees of various commercial banks. In the present research study, I found that there is a positive and significant relationship between emotional intelligence and job satisfaction of employees working in commercial banking sector.